Improving the Quality of Bleeder Parts With QC Seven Tools and Kaizen at PT Hitachi Astemo Bekasi Brake Systems - Suara, Jaka; Tri Ngudi Wiyatno (MultiTech Publisher, 2024)
PT Hitachi Astemo Bekasi Brake Systems Indonesia, an automotive manufacturing company which is the main vendor of PT Astra Honda Motor, has experienced an increase in the number of rejected part bleeders in its production process. Data shows a significant increase in the number of rejects over the last 3 months, reaching 13% of total production, with a time loss impact of around 2.6 days in 3 months. The research results show that after making improvements using the QC Seven Tools method and the Kaizen approach, the company succeeded in reducing the reject rate on part bleeders significantly. The rejection rate, which previously averaged 4.4%, equivalent to 1,308 pcs per month, was successfully reduced to only 0.01%, equivalent to 4 pcs per month. This shows the effectiveness of applying these methods in improving product quality and production process efficiency. This research makes an important contribution to companies in identifying and overcoming product quality problems effectively, as well as strengthening competition in the automotive market.